Effectiveness of video tutorial on compliance of medical officers to sequence of intubation protocol in simulated Covid-19 patients - Mohamad Azlan Awang; Rhendra Hardy Mohamad Zaini; Wan Mohd Nazaruddin Wan Hassan (Malaysian Journal of Anaesthesiology, 2022)
The use of full PPE, aerosol box, and video laryngoscope are recommended when performing intubation on a Covid-19 patient. However, this technique may be difficult for medical officers unfamiliar with the intubation protocol sequence, especially for those with less experience in anaesthesia. Video tutorials may play a vital role in improving the technique. This study evaluated the compliance of medical officers in our anaesthesia department to the intubation protocol and the effect on compliance before and after viewing the video tutorial on the protocol. A total of 70 medical officers (n = 70) in the Department of Anaesthesia, Hospital Universiti Sains Malaysia, Kelantan participated in this study. The participants performed the intubation protocol sequence on a simulated Covid-19 mannequin. Participants then viewed a video tutorial after their initial attempt and repeated the intubation sequence afterward. The outcomes measured include the proportion of participants compliant with the intubation protocol, the association between years of experience and compliance, and the compliance score before and after the video tutorial. There was no significant association between years of anaesthesia and compliance score (p = 0.058). A large proportion of the subjects were compliant (n = 57, 81.4%). There was a significant difference between initial and repeated compliance score post-video tutorial (p < 0.05). Years of experience in anaesthesia was not a determining factor for compliance with the intubation protocol sequence on simulated Covid-19 patients. However, the video tutorial played a significant role in improving compliance with the intubation sequence.